ΔNp63 is regulated by insulin/IGF-1 signaling in normal basal/progenitor mammary cells and in luminal-type breast cancer cells - Stenckova, Michaela; Liu, Yajing; Nekulova, Marta; Holcakova, Jitka; Pokorna, Zuzana; Nenutil, Rudolf; Thompson, Alastair M; Vojtesek, Borivoj; Coates, Philip John (Neoplasma, 2023)
Breast cancers are a heterogeneous group of tumors classified according to their histological growth patterns and receptor expression characteristics. Intratumor heterogeneity also exists, with subpopulations of cells with different phenotypes found in individual cancers, including cells with stem or progenitor cell properties. At least two types of breast cancer stem cells (CSCs) exist, the epithelial and the basal/mesenchymal subtypes, although how these phenotypes are controlled is unknown. ΔNp63 is a basal cell marker and regulator of stem/progenitor cell activities in the normal mammary gland and is expressed in the basal-like CSC subpopulation in some estrogen receptor-positive (ER+) and/or human epidermal growth factor receptor 2-positive (HER2+) breast adenocarcinomas. Whilst p63 is known to directly impart CSC properties in luminal breast cancer cells, how p63 is regulated and induced in these cells is unknown. We initially confirmed the existence of a small subpopulation of ΔNp63+ cells in lymph node metastases of ER+ human ductal adenocarcinomas, indicating together with previous reports that ΔNp63+ tumor cells are present in approximately 40% of these metastases. Notably, ΔNp63+ cells show a preferential location at the edge of tumor areas, suggesting possible regulation of ΔNp63 by the tumor microenvironment. Subsequently, we showed that the high levels of ΔNp63 in basal non-transformed MCF-10A mammary epithelial cells rely on insulin in their culture medium, whilst ΔNp63 levels are increased in MCF-7 ER+ luminal-type breast cancer cells treated with insulin or insulin-like growth factor 1 (IGF-1). Mechanistically, small molecule inhibitors and siRNA gene knockdown demonstrated that induction of ΔNp63 by IGF-1 requires PI3K, ERK1/2, and p38 MAPK activation, and acts through FOXO transcriptional inactivation. We also show that metformin inhibits ΔNp63 induction. These data reveal an IGF-mediated mechanism to control basal-type breast CSCs, with therapeutic implications to modify intratumor breast cancer cell heterogeneity and plasticity.
Keywords: Adenocarcinoma; Female; inzuliny; Tumor Microenvironment; nádory prsu; lidé; Insulin-Like Growth Factor I; Insulins; Breast Neoplasms; Stem Cells; ženské pohlaví; adenokarcinom; nádorové mikroprostředí; Humans; insulinu podobný růstový faktor I; kmenové buňky